Bioactive metabolites from Chaetomium aureum: Structure elucidation and inhibition of the Hsp90 machine chaperoning activity. Issue 1 (1st January 2015) - Kabbaj, Fatima Zahra; Lu, Su; Faouzi, My El Abbés; Meddah, Bouchra; Proksch, Peter; Cherrah, Yahya; Altenbach, Hans-Josef; Aly, Amal H.; Chadli, Ahmed; Debbab, Abdessamad
Graphical abstract: Abstract: Chemical investigation of the EtOAc extract of the fungus Chaetomium aureum, an endophyte of the Moroccan medicinal plant Thymelaea lythroides, afforded one new resorcinol derivative named chaetorcinol, together with five known metabolites. The structures of the isolated compounds were determined on the basis of one- and two-dimensional NMR spectroscopy and high-resolution mass spectrometry as well as by comparison with the literature. All compounds were tested for their activity towards the Hsp90 chaperoning machine in vitro using the progesterone receptor (PR) and rabbit reticulocyte lysate (RRL). Among the isolated compounds, only sclerotiorin efficiently inhibited the Hsp90 machine chaperoning activity. However, sclerotiorin showed no cytotoxic effect on breast cancer Hs578T, MDA-MB-231 and prostate cancer LNCaP cell lines. Interestingly, deacetylation of sclerotiorin increased its cytotoxicity toward the tested cell lines over a period of 48 h.